Hypertension impairs neurovascular coupling and promotes microvascular injury: role in exacerbation of Alzheimer’s disease - Csiszar, Anna (GeroScience, 2017)
Hypertension in the elderly substantially increases both the risk of vascular cognitive impairment (VCI) and Alzheimer’s disease (AD); however, the underlying mechanisms are not completely understood. This review discusses the effects of hypertension on structural and functional integrity of cerebral microcirculation, including hypertension-induced alterations in neurovascular coupling responses, cellular and molecular mechanisms involved in microvascular damage (capillary rarefaction, blood-brain barrier disruption), and the genesis of cerebral microhemorrhages and their potential role in exacerbation of cognitive decline associated with AD. Understanding and targeting the hypertension-induced cerebromicrovascular alterations that are involved in the onset and progression of AD and contribute to cognitive impairment are expected to have a major role in preserving brain health in high-risk older individuals.